The Potential of Traditional Medicine in Combating COVID-19: A Systematic Review and Meta-Analysis - Amin, Tasbir; Hossain, Amana; Jerin, Nusrat; Mannan, Shahnewaj Bin; Akter, Noor Jahan; Hossain, Murad; Ahmed, Monir Uddin; Jime, Jinath Sultana; Bulbul, Nayeema; Safa, Ashrafus; Shishir, Md. Asaduzzaman; Fakruddin, Md. (Coronaviruses, 2025)
ObjectivesThe aim of the study was to review the existing data on traditional medicine in reducing the symptoms in COVID-19 patients with mild, moderate, and severe symptoms. We also investigated the adverse impact, patient outcome, source, and mode of action of traditional medicine. A brief comparison was made on adverse impacts and symptom alleviation of the commercially available drugs as well.MethodsWe utilized PubMed, Scopus, WHO Global Health Library (GHL), and Virtual Health Library (VHL) in order to choose the eligible studies for the systematic review between July and August 2022. From a total of 12,263 studies, after a series of screening, 285 articles were identified in the final sample. The methodological evaluation was carried out accordingly.ResultsThere is a growing literature on the usage of traditional medicine for COVID-19. The majority of the studies have shown positive outcomes even though they were not carried out at diverse locations around the world. We identified that the majority (17.4%) of the traditional medicine was derived from plants. The average time in the disappearance of the symptoms was 8.8 days, whereas the disappearance of symptoms using conventional drugs (Remdesivir, Ivermectin, Tocilizumab, Baricitinib, Famotidine, Ensitrelvir and Molnupiravir) was around 12 days. The mode of action of traditional medicine was mostly the reduction of viral load (50%). In terms of the severity of the patients, most of the patients (37.5%) had mild symptoms. We also found that no major adverse impact was reported on administering the traditional medicine among the patients. Further, the majority of the study was carried out in the Asian region, mostly in China.ConclusionApart from expanding the study to different regions of the world, to improve the quality of data, larger-scale clinical studies in the Asian region are required.
Keywords: traditional medicine